SEMIOTIC IN MILK ADVERTISEMENTS - Roisa Monika Manurung; Siti Aisyah Ginting; I Wayan Dirgeyasa Tangkas (LINGUISTIK TERAPAN, 2021)
Television advertisement has a promotional function as a medium to advertise a product. It implicitly persuades people to create demand of a product that is being advertised. Implicit meaning can be studied with semiotic; it is the theory and study of sign, symbol, and signification as communicative behavior, especially as elements of language or other system of communication. This study is aimed to identify the types of signs of milk television advertisements. The writer focuses on four advertisements of milk products 'Bear Brand Sterilized advertisements, which published on television media since June 2009-2015. The methodology used in this research is qualitative method and the researcher uses semiotics approach of Charles Sanders Peirce. The data of this analysis are phrases, sentences, images, objects, and colors in each advertisement. The writer identifies some signs in each scene of the advertisement. The data are found in 25 in the bear brand advertisements. The result of this study shows that each scene contains signs such as icon,index, and symbol. There are 22 of icons, 8 indexes, and 26 symbols. In the analysis using Charles Sanders Pierce Triadic theory, the writer found that in every advertisement uses signs which consist of representament, object, and interpretant. The combination of the three signs will deliver the meaning of the selected object (advertisement) to the reader. The result of the study shows that the three kinds of signs are used to create clear meanings and both of them have a strong relationship in delivering messages of the products.Keywords: Television Advertisement, Semiotic, Icon, Index, Symbol